Conceptual debates on initial reading instruction and literacy - Valente, Paula Rejane de Araújo; Miki, Pérsida da Silva Ribeiro (Seven Editora, 2024)
This text explores the concepts of literacy, literacy and literacy through a qualitative approach. The methodology used included bibliographic and documentary analysis to achieve the proposed objectives. The study sought to understand the conceptual differences between literacy, literacy and literacy, based on bibliographic reviews of works by Soares (2009, 2017a, 2017b, 2020), Kleiman (1995, 2005) and Tfouni (2002, 2018). In addition, the study proposed a debate on the approximation and opposition of these concepts in the official documents that guide educational policies for the teaching of reading and writing in Brazil, such as the National Curriculum Parameter of Portuguese Language (PCNs LP), the National Common Curricular Base (BNCC), Decree No. 9,765 of 04/11/2019, which instituted the National Literacy Policy, and the Guiding Notebook of the National Literacy Policy (PNA). As a result, the terms literacy, literacy and literacy play important roles in educational practices, being found both in normative teaching documents and in continuing education activities for teachers (Pró-Letramento and PNAIC). It is worth mentioning that they are not teaching methods nor synonymous, as each one has its own specificity, although they are closely related. Thus, it is crucial that education professionals who plan pedagogical actions in the process of teaching reading and writing can clearly identify these terms. DOI:https://doi.org/10.56238/sevened2024.018-016